FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN PENGGUNAAN ALAT PELINDUNG DIRI PADA PETUGAS PENANGANAN PRASARANA SARANA UMUM DI KELURAHAN CAWANG TAHUN 2023 - Galuh Putri Kusuma Astuti (2023)
PPE is an effort to prevent occupational diseases and accidents due to occupational hazards and risks for Public Infrastructure and Facilities Handling Officers (PPSU) in Cawang Subdistrict. The research aims to obtain the factors associated to PPE compliance by PPSU workers in Cawang Subdistrict. The research was conducted using quantitative analytic methods with a cross-sectional study design. The samples were 79 respondents which was selected based on purposive sampling technique. The research instrument used questionnaires and observation sheets. The results of the study using the logistic regression test showed that education (p-value = 0.014) and OSH regulations (p-value = 0.046) have an association with PPE compliance. The variables of age, years of service, knowledge, attitudes, perceptions, and K3 training have no association to PPE compliance. Based on the multivariate analysis, the most dominant variable was education (POR=6.088). It can be inferred that the variables associated to PPE compliance were education and OSH regulations, in which education was the most dominant variable. It is recommended to make obvious regulations or SOPs regarding PPE standards, types of PPE according to work, and sanctions related to PPE that are easily accessed by PPSU officers and carry out stricter supervision while working.